Magnetic and Radioactive Nanoparticles for Improved Theranostics and AI Assisted Radiation Therapy - Gizachew Diga Milki (International Journal of Advance in Molecular Engineering, 2025)
Nanoparticles based therapeutic and theranostics technique is becoming an active area of research in nanomedicine. The sensitivity, biocompatibility, and stability of magnetic and radioactive nanoparticles determine their functionality. This research highlights the impacts of magnetic and radioactive nanoparticles on therapeutic techniques namely, cell therapy, gene therapy, and tissue regeneration. Then, it is intended to brief a principal role of these therapeutic techniques to envisage theranostics medicine and radiation therapy using the nanoparticles. Currently, a therapeutic and theranostics technique based on magnetic and radioactive nanoparticles is becoming an efficient treatment method for cancer and malignant disease. Moreover, the potential role of magnetic and radioactive nanoparticles in combined effect of diagnostics and imaging is seen. Customary, nanoparticles are investigated for magnetic fluid hyperthermia, magnetic resonance imaging, and theranostics. Moreover, they are good candidate of nano based drug delivery, nanocarriers, and nanozymes. The futures of such therapeutic technique have greater commitment on the AI assisted radiation therapy, theranostics, and drugs delivery system. In turn, the significance of theranostics medicine is investigated for the treatment of epidemics such as atherosclerosis, brain cancer, breast cancer, and cardiovascular disease.Furthermore, ongoing studies reveal that nanoparticle-mediated therapies can be designed with surface modifications to achieve higher selectivity, minimizing systemic toxicity while maximizing therapeutic efficacy. Functionalization with ligands, antibodies, or peptides allows nanoparticles to actively target diseased cells, enhancing precision medicine approaches. Recent advances in multimodal imaging show that nanoparticles can simultaneously provide diagnostic information and therapeutic intervention, offering a real-time monitoring capability. This dual function not only accelerates the decision-making process for clinicians but also improves patient outcomes by enabling adaptive treatments. As research progresses, integration with machine learning and computational models is expected to refine nanoparticle design, optimize dosages, and predict therapeutic responses. Overall, magnetic and radioactive nanoparticles present a transformative pathway toward personalized, efficient, and safer healthcare systems, bridging the gap between conventional medicine and futuristic nanotheranostics.
Keywords: AI; Cancer; Cardiovascular disease; Therapy; drug delivery; magnetic nanoparticles; radioactive nanoparticles; theranostics